THE IMPACT OF CORPORATE CULTURE ON CHINESE CATERING: A CASE STUDY - Li Rong Hui; Komm Pechinthorn; Nico Irawan; Patida Limchaicharoen (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This paper aims to discuss the impact of corporate culture on a company and how better to align corporate culture with the firm's development. The corporation's mission, purpose, spirit, values, and business philosophy contribute to developing the corporate culture. Corporate culture is the essence of an organization and an irrepressible engine of growth. It is dense with information and is concentrated on the company's values and spirit. Corporate culture is centered on values. If the corporate culture is exhibited through common behaviors, it will have a distinct competitive advantage and rapid growth. As the research object, we explained the fundamental theory of enterprise culture, the construction of Haidilao enterprise culture following the management present situation investigation questionnaire results, and the structure of Haidilao enterprise culture following the questionnaire results. Haidilao has made remarkable strides in the last decade as a result of its corporatization achievements. However, Haidilao's present corporate culture management challenges are affecting the company's growth significantly.